Evaluation of ameliorative potential of antioxidants and/or immunomodulators in contagious caprine pleuropneumonia affected Himalayan Pashmina goats - PARRAY, OVEAS RAFFIQ; MUHEET; BHAT, RIYAZ AHMAD; MALIK, HAMID ULLAH; QURESHI, SABIA; BEIG, SHAFAYAT AHMAD; NAZIR, QURAT UL AIN; KAWOOSA, MAJID SHAFI; RATHER, IZHAR AHMAD; MUHEE, AMATUL; SHAFI, TAWHEED; YATOO, MOHD IQBAL (The Indian Journal of Animal Sciences, 2023)
Contagious caprine pleuropneumonia causes oxidative stress and immune disturbances in affected goats. Hence these derogative alterations aggravate the pathogenesis and severity of this disease, thus, necessitating utilization of antioxidants and/or immunomodulators in the therapeutic regimes of contagious caprine pleuropneumonia. Present study evaluated ameliorative effects of N-acetyl cysteine (NAC) and alpha tocopherol (vitamin E) in association with primary antibiotic tylosin treatment in contagious caprine pleuropneumonia affected test goats in comparison to antibiotic only treated goats (n=6) and healthy goats (n=6). N-acetyl cysteine given at a dose of 12 mg per kg of body weight orally daily for 7 days, showed better antioxidant effect by significantly ameliorating oxidative stress (41.4%) compared to other treatments; besides, decreasing total oxidative status (TOS) and increasing total antioxidant status (TAS). Immunomodulatory potential of alpha tocopherol given at a dose of 10 mg per kg of body weight orally daily for 7 days, was found to be comparatively better than NAC in decreasing percentage of neutrophils and increasing percentage of lymphocytes; besides, decreasing the levels of tumor necrosis factor-α (TNF-α) and immunoglobulin G (IgG) when the modulation of total leukocyte count and differential leukocyte count was comparable between the two. Thus, it can be concluded from this study that NAC acts as a comparatively better antioxidant and alpha tocopherol as better immunomodulator when used in the therapeutic regimes of contagious caprine pleuropneumonia.